Where have you gone, Joe DiMaggio? - HBO Video (Firm) (New York : HBO Home Video, 2002)
The story of Joe DiMaggio, one of the few men to truly define the spirit of baseball.
Hi/Fi ; Dolby Surround.
For specific features see interactive menu.
Executive producer, Ross Greenburg ; coordinating producer, Kirby Bradley ; editor, Andrew Morreale ; original music by Camara Kambon.
DVD.
Keywords: DiMaggio, Joe, -- 1914-1999.; Baseball players -- Biography; Documentary films